Antioxidant Activity of Nannochloropsis sp. Biopigments Extracted by Soybean Oil - Nafisah Sholihah, Prasetyana
Antioxidants are a molecule that inhibit the oxidation of other molecule producing free radicals. Antioxidant activity is expressed in IC50 value. So far, antioxidant activity of biopigments of microalgae Nannochloropsis sp. are not widely explored yet. The objective of the present study was to determine the antioxidant activity of Nannochloropsis sp. biopigments extracted by soybean oil as a solvent. The research methods included cultivation of Nannochloropsis sp. in modification medium, extraction of Nannochloropsis sp. biopigments with soybean oil as a solvent, purification of the biopigments using silica column chromatography, characterization of the biopigments with UV-Vis spectrophotometry, and determination of the antioxidant activity of biopigments on radical substrates: 2,2-diphenyl-1 picrylhydrazyl (DPPH) and radical 2,2'- Azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS). The results showed that culture of Nannochloropsis sp. cells with an initial density of 0.5 × 106 cells/mL for 8 d produced dried biomass yield of 0.2±0.06 g/L. Total carotenoids extracted from one gram dried Nannochloropsis sp. biomass was 58.83±13.4 mg. Of 44 total fractions obtained, 5 Nannochloropsis sp. biopigments were identified as pure biopigment fractions: ?- carotene, pheophytin a, chlorophyll a, lutein, and violaxanthin. The IC50 value of crude extract, ?-carotene, and pheophytin a of Nannochloropsis sp. against DPPH was 142.56, 26.81, and 41.13 µg/mL, respectively, and against ABTS was 84.75, 8.94, and 10.20 µg/mL, respectively. Overall, ?-carotene exhibited the highest antioxidant activity.